Poverty risk and management strategies for rural patients with the chronic diseases known as the "3 highs" in underdeveloped areas - GUO Xucheng; XIE Zhuodan; YUAN Ping (Yixue xinzhi zazhi)
Objective To analyze the risk and management strategy of poverty and return to poverty in patients with the chronic diseases known as the "3 highs" in underdeveloped areas.Methods This study used the field survey data of rural patients with the "3 highs" in an underdeveloped area as an example and has combined it with the social ecosystem theory. The paper then analyzes and explores the risks of poverty and return to poverty caused by illness among patients with the "3 highs" from three aspects: micro-system—patient's personal health literacy, meso-system—interaction between patients and healthy family members and the macro-system—medical policy for these patients.Results A total of 198 patients with chronic diseases known as the "3 highs" in seven villages were included in the study, with an average age of 58 years. The majority had hypertension (48.5%) and diabetes (41.4%). 126 people (63.6%) think that knowledge of prevention strategies can only help patients to take effective measures when they are ill, 11 people (5.6%) think that knowledge of prevention strate-gies is useless under normal health conditions, 91 people (46.0%) think that illness has an important impact on work and life, and 12 people (6.1%) spend more than 60% of family income on illness.Conclusion Patients with the "3 highs" are faced with poverty worries due to low health literacy, which is compounded by damaged family human capital, catastrophic expenditure caused by the deterioration of their condition and other reasons. We can consider starting from the three areas explored: raising these patients’ health literacy, improving the overall human capital of families with chronic diseases, and building a multi-field coordinated health security system to prevent these patients from becoming poor or returning to poverty due to illness.